Development Strategy and Franchise Based Business Model at Beverage Shop of JR Tea Makassar - Rizkia Afni; Tuti Supatminingsih; Muhammad Hasan; Mustari Mustari; Muhammad Dinar (HUMAN: South Asian Journal of Social Studies, 2021)
This study aims to identify and analyze development strategies and franchise-based business models in the JR Tea Makassar Beverage Shop. The research method used is a qualitative descriptive research approach using data collection methods through observation, interviews, and documentation of the research object which is then analyzed using SWOT analysis. Based on the results of the study, it shows that the strategy implemented by the JR Tea Makassar Beverage Shop is in accordance with the SWOT analysis which is in quadrant I, which is an aggressive strategy with the implementation of a strategy (growth oriented strategy) which is a very profitable situation with the implementation of SO strategy implementation policies then implemented in designing the business model canvas by building value propositions, customer relationships, and channels in the business model canvas block and then moving to the segment block